Building Bridges between Perceptual and Economic Decision-Making: Neural and Computational Mechanisms - Summerfield, Christopher; Tsetsos, Konstantinos (Frontiers in Neuroscience, 2012)
Investigation into the neural and computational bases of decision-making has proceeded in two parallel but distinct streams. Perceptual decision making (PDM) is concerned with how observers detect, discriminate and categorise noisy sensory information. Economic decision making (EDM) explores how options are selected on the basis of their reinforcement history. Traditionally, the subfields of PDM and EDM have employed different paradigms, proposed different mechanistic models, explored different brain regions, disagreed about whether decisions approach optimality. Nevertheless, we argue that there is a common framework for understanding decisions made in both domains, under which an agent has to combine sensory information (what is the stimulus) with value information (what is it worth). We review computational models of the decision process typically used in PDM, based around the idea that decisions involve a serial integration of evidence, and assess their applicability to decisions between good and gambles. Subsequently, we consider the contribution of three key brain regions – the parietal cortex, the basal ganglia, and the orbitofrontal cortex – to perceptual and economic decision-making, with a focus on the mechanisms by which sensory and reward information are integrated during choice. We find that although the parietal cortex is often implicated in the integration of sensory evidence, there is evidence for its role in encoding the expected value of a decision. Similarly, although much research has emphasised the role of the striatum and orbitofrontal cortex in value-guided choices, they may play an important role in categorisation of perceptual information. In conclusion, we consider how findings from the two fields might be brought together, in order to move towards a general framework for understanding decision-making in humans and other primates.